Modeling of low-frequency modal noise induced by multimode couplers in cascade connections - Maksymiuk, Łukasz; Siuzdak, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this paper, we present a theory concerning low-frequency modal noise in the cascade of couplers. This theory enables calculation of signal-to-noise ratio in cascade connection of multimode couplers. We provide a series of numerical calculations based on the model for different realizations of the couplers.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 649-660
Keywords: optyka; modal noise; multimode fiber; multimode coupler; passive optical network (PON)